Project approach: Facilitating elementary school students in reading - Santhi, Dessy Dwi Yudha (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
Metaphors in a written discourse such as in letters using bahasa Indonesia can be derived from the metaphorical expressions used by the writers to the editors, showing conceptualization based on what they experience, feel, and think in their lives. This paper aims at finding out the universality of the concepts shown by the metaphors and the users employing them. Using nonparticipant observation with a note-taking technique, the data are collected and selected purposively. With distributional, referential, reflective introspective, and abductive inferential methods, the data are analyzed. The results indicate that metaphors can be grouped into universal, specific, and public ones due to the universality and specification of the concepts conveyed, as well as the users employing them. This implies that bahasa Indonesia conveys similar concepts to those of other languages in the world, which is caused by experiences from different times and places encountered by Indonesians living in an agricultural country.